2021
DOI: 10.3389/fpsyt.2021.747648
|View full text |Cite
|
Sign up to set email alerts
|

Higher Acceptance of Videotelephonic Counseling Formats in Psychosomatic Medicine in Times of the COVID-19 Pandemic

Abstract: Background: Due to the COVID-19 pandemic, the healthcare system in general and psychosomatics in particular were forced to change counseling-specific services and break up established structures. At the beginning of 2020, phone as well as videotelephonic counseling options had to be quickly established.Methods: Patients (n = 278) of the department of psychosomatic medicine and psychotherapy at the University Hospital Tübingen were asked to complete an ad hoc questionnaire to assess the acceptance of the counse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Patient use was examined in 10 studies [ 41 , 43 , 44 , 50 , 53 , 54 , 56 , 57 , 59 , 60 ], patient satisfaction in 7 studies [ 45 , 46 , 48 , 49 , 51 , 52 , 55 ], and both outcomes were observed in 3 studies [ 42 , 47 , 58 ]. Patient use was mostly defined as having at least 1 telemental health visit during the pandemic [ 43 , 44 , 53 , 54 , 56 , 58 - 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient use was examined in 10 studies [ 41 , 43 , 44 , 50 , 53 , 54 , 56 , 57 , 59 , 60 ], patient satisfaction in 7 studies [ 45 , 46 , 48 , 49 , 51 , 52 , 55 ], and both outcomes were observed in 3 studies [ 42 , 47 , 58 ]. Patient use was mostly defined as having at least 1 telemental health visit during the pandemic [ 43 , 44 , 53 , 54 , 56 , 58 - 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, others have also considered the number of telemental health visits [ 42 , 53 , 54 , 57 ] and the percentage of telemental health services in overall mental health service use during the pandemic [ 41 , 44 ] or attendance [ 47 , 50 ]. For patient satisfaction, 6 studies used self-developed items and scales [ 42 , 45 , 49 , 51 , 52 , 58 ], whereas 4 studies used established instruments (ie, Telemedicine Satisfaction Questionnaire [ 61 ], Client Satisfaction Questionnaire [ 62 ], Patient Satisfaction Questionnaire [ 63 ], Treatment Perception Questionnaire [ 64 ], and Internet Evaluation and Utility Questionnaire [ 65 ]) [ 46 - 48 , 55 ]. The satisfaction questionnaires mainly focused on the overall satisfaction with the services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lower perception of negative effects due to the COVID-19 pandemic in patients with schizophrenia compared to other diagnosis groups was also reported in other studies [ 28 , 33 , 37 , 50 ]. An explanation for these counterintuitive results could be that the restrictions in public life following lockdown measures were associated with lower levels of social and environmental stress, while the limitations in face to face treatment contacts in many countries were substituted by digital media consultation [ 74 79 ]. Nevertheless, our results also indicate that perceived negative effects of the COVID-19 pandemic increase with increasing level of functional impairment due to mental disorders, at least on the dimensions of physical and emotional well-being, partnership, housing situation, and expectations for the future but also on the PICOV19 score.…”
Section: Discussionmentioning
confidence: 99%
“…following lockdown measures were associated with lower levels of social and environmental stress, while the limitations in face to face treatment contacts in many countries were substituted by digital media consultation [74][75][76][77][78][79]. Nevertheless, our results also indicate that perceived negative effects of the COVID-19 pandemic increase with increasing level of functional impairment due to mental disorders, at least on the dimensions of physical and emotional well-being, partnership, housing situation, and expectations for the future but also on the PICOV19 score.…”
Section: Plos Onementioning
confidence: 99%